33.5k views
1 vote
Perform the indicated operation.

(4g²-9) ÷ (2g-3)

A. 2g-3

B. 2g+3

C. 2g+3 R 18​

User Clhy
by
4.7k points

1 Answer

1 vote

Answer:

Solving
(4g^2-9) / (2g-3) we get 2g+3

Option B is correct.

Explanation:

We need to solve
(4g^2-9) / (2g-3)

We know that
a^2-b^2=(a-b)(a+b)

So,
4g^2-9 can be written as
(2g)^2-(3)^2

So, using above formula we will get:


4g^2-9\\=(2g^2)-(3)^2 \\Using \ formula a^2-b^2 = (a-b)(a+b)\\=(2g-3)(2g+3)

So, numerator will become


((2g-3)(2g+3))/((2g-3)) \\Simplifying:\\=2g+3

So, solving
(4g^2-9) / (2g-3) we get 2g+3

Option B is correct.

User Zud
by
5.1k points